Study on Influencing Factors of Consistency in Manufacturing Process of Vehicle Lithium‐Ion Battery Based on Correlation Coefficient and Multivariate Linear Regression Model. Issue 8 (3rd July 2021) - Han, Youjun; Yuan, Hongyuan; Li, Jin; Du, Juan; Hu, Yueming; Huang, Xuejie
Abstract: Lithium‐ion battery manufacturing is a multiprocess serial system and the consistency of each single cell will affect the performance and safety of battery system after grouping. Therefore, optimizing the battery preparation process and improving the battery consistency have become the key technical issues in battery preparation process. In this study, the inconsistency of finished batteries caused by manufacturing process is analyzed from three processes: electrode preparation, battery assembly, and liquid injection and formation and the structure–activity relationship between manufacturing process data and battery consistency is studied. Taking the actual capacity, self‐discharge rate, and internal resistance of single cell as target variables, the correlation coefficient matrix between original process variables and target variables is constructed by using correlation analysis method and the correlation index between process variables and target variables is obtained. The multiple linear regression model is established by stepwise regression method and the weight of original process variables affecting battery consistency is deduced. The results show that the data of multiple process links have a high influence weight on the actual capacity and self‐discharge rate of batteries, which provide a theoretical model for the key strategies of improving quality consistency in lithium‐ion battery industry. Abstract : The correlation coefficient analysis and multiple regression model are applied to establish the structure–property relationship between the manufacturing processes and the consistency of single cell in lithium‐ion battery. Consequently, it points out the strategy of improvement and optimization to enhance the consistency of lithium‐ion battery in manufacturing process.